1998
DOI: 10.1111/j.1600-0447.1998.tb10000.x
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate mental health

Abstract: This paper reviews the historical aspects of expatriate mental health, and comments on the paucity of literature in the medical and psychiatric journals. Data obtained from 397 expatriate probands examined during overseas service are described. It was noted that there was a high incidence of affective and adjustment disorders. The results showed six areas significantly related to those with affective disorders at interview, namely a history of consultation for psychological problems in out-patient departments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 6 publications
2
27
0
Order By: Relevance
“…Lifestyle factors have been reported to influence both physical health [1][2][3][4] and mental health 3,5,6) . Although living and working abroad has been shown to be associated with many challenges that could adversely affect their mental health [7][8][9][10] , the incidence of mental health problems among Japanese overseas workers and their accompanying spouses is not precisely known.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle factors have been reported to influence both physical health [1][2][3][4] and mental health 3,5,6) . Although living and working abroad has been shown to be associated with many challenges that could adversely affect their mental health [7][8][9][10] , the incidence of mental health problems among Japanese overseas workers and their accompanying spouses is not precisely known.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,10 In a review of the literature, Foyle and Watson reported a high incidence of affective and adjustment disorders among career missionaries. 10,25 The PRISM Study found 60.1 and 65.8% of men and women to have experienced a moderate to serious bout of anxiety, and 45.0 and 55.5% of men and women to have experienced a moderate to serious bout of depression.…”
Section: Mental Healthmentioning
confidence: 99%
“…7,8,10 In a review of the literature, Foyle and Watson reported a high incidence of affective and adjustment disorders among career missionaries. 10,25 The PRISM Study found 60.1 and 65.8% of men and women to have experienced a moderate to serious bout of anxiety, and 45.0 and 55.5% of men and women to have experienced a moderate to serious bout of depression. 26 As a baseline for comparison, the lifetime prevalence of depression among physicians in the U.S. is 12% for men age 45-54 and 19.5% for women, although the method of measurement used was different from that used in the PRISM Study.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we assume as expatriates the employees who are sent by their organization to work in one of its foreign branches or subsidiaries (Siers, 2007) to accomplish a job-related goal (Sinangil & Ones, 2003). When their assignment is completed they return to their original country (Foyle, Beer, & Watson, 1998). This assignment can be a short-term international one, defined as a "temporary internal transfer to a foreign subsidiary of between one and twelve months duration" (Collings, Scullion, & Morley, 2007, p. 205) or a long-term international assignment.…”
mentioning
confidence: 99%